L’INDIVIDU, UN SUJET DE DROIT OU UN ANIMAL SYMBOLIQUE ? MALAISE DANS LE DROIT - AMAR, Jacques (Studia Universitatis Babeș-Bolyai Philosophia, 2020)
The individual, a subject of law or a symbolic animal? Discomfort in the law. How can it be explained that the text concerning the prohibition of religious signs in the public sphere in France can be justified in the name of human rights in France and condemned in the name of human rights at the United Nations? The present article attempts to explain this situation on the basis of the notion of dispute expounded by J. F. Lyotard; it tries to explain the new trends in contemporary law on the basis of the distinction between dispute and litigation.